Reemergence of dengue: a great challenge for the health Latin American and Caribbean system, in the middle of XXI century - Osmany Enrique Tamayo Escobar; Tania María García Olivera; Nilia Victoria Escobar Yendez; Daniel González Rubio; Osvaldo Castro Peraza (Centro Provincial de Información de Ciencias Médicas, 2019)
An up-dating review on dengue was carried out, fundamentally centered in the Region countries, keeping in mind that it is a reemerging infectious disease, which still represents a public health problem of universal scale, more and more common and disseminated in tropical and subtropical areas, due to its demographic and climatological conditions.